Brain drain in Türkiye’s nursing workforce: A literature review: Nursing brain drain - Şişik, Seher; Karabacak, Bilgi Gülseven (Journal of Surgery and Medicine, 2025)
Nurses represent the largest workforce group forming the foundation of global health systems. Despite this central role, a critical worldwide nursing shortage persists, posing significant threats to the sustainability of health systems, particularly in low- and middle-income countries. Although Türkiye’s nursing workforce has expanded in recent years, it remains far below OECD (Organization for Economic Co-operation and Development) averages and struggles to meet the growing demand for healthcare services. This review adopts a comprehensive approach to examine the economic, organizational, social, and psychological factors accelerating nurse brain drain from Türkiye, drawing on national and international data. Findings indicate that low wages, heavy workloads, insufficient staffing, workplace violence, limited career opportunities, and burnout serve as major push factors influencing nurses’ decision to migrate. Conversely, high-income countries such as Germany, the Netherlands, Canada, and the United Kingdom offer strong pull factors including higher salaries, safer working environments, lower nurse-to-patient ratios, and well-developed professional career pathways. While Türkiye’s migration patterns share similarities with nurse-exporting countries such as the Philippines and India, high rates of workplace violence and the emigration of experienced nurses place Türkiye in a distinct position. Nurse brain drain has immediate consequences, including increased workload and negative impacts on patient safety, and long-term effects such as loss of institutional memory and transfer of educational investments to receiving countries. This review underscores the need for policy development addressing the structural drivers of nurse brain drain and provides a critical situational analysis for the future of Türkiye’s healthcare system.